Adaptation and uptake evaluation of an SMS text message smoking cessation programme (MiQuit) for use in antenatal care. Issue 10 (22nd October 2015) - Naughton, Felix; Cooper, Sue; Bowker, Katharine; Campbell, Katarzyna; Sutton, Stephen; Leonardi-Bee, Jo; Sloan, Melanie; Coleman, Tim
Abstract : Objectives: To adapt a tailored short message service (SMS) text message smoking cessation intervention (MiQuit) for use without active health professional endorsement in routine antenatal care settings, to estimate 'real-world' uptake and test the feasibility of its use. Design: Single-site service evaluation. Setting: A Nottinghamshire (UK) antenatal clinic. Participants: Pregnant women accessing the antenatal clinic (N=1750) over 6 months. Intervention: A single-sheet A5 leaflet provided in the women's maternity notes folder describing the MiQuit text service. Similar materials were left on clinic desks and noticeboards. Outcome measures: MiQuit activation requests and system interactions were logged for two time frames: 6 months (strict) and 8 months (extended). Local hospital data were used to estimate the denominator of pregnant smokers exposed to the materials. Results: During the strict and extended time frames, 13 and 25 activation requests were received, representing 3% (95% CI 2% to 5%) and 4% (95% CI 3% to 6%) of estimated smokers, respectively. Only 11 (44%) of the 25 requesting activation sent a correctly formatted initiation text. Of those activating MiQuit, and invited to complete tailoring questions (used to tailor support), 6 (67%) completed all 12 questions by text or website and 5 (56%) texted a quit date to the system. Of the 11 activating MiQuit, 5 (45%, 95% CI 21% to 72%) stopped the programme prematurely. Conclusions: A low-intensity, cheap cessation intervention promoted at very low cost, resulted in a small but potentially impactful uptake rate by pregnant smokers.